2023
DOI: 10.3390/healthcare11101412
|View full text |Cite
|
Sign up to set email alerts
|

Coping Mechanisms during the War in Ukraine: A Cross-Sectional Assessment among Romanian Population

Cătălina Angela Crișan,
Zaki Milhem,
Roland Stretea
et al.

Abstract: On 24 February 2022, the Russian Federation invaded Ukraine, starting a military conflict that soon turned into a full-scale war. The Romanians have been actively involved in helping their neighbors, causing the accumulation of emotional and mental pressure upon the Romanian population exposed to such a close military conflict. This cross-sectional study assessed, through an online survey (1586 adult Romanian residents), the primary coping mechanisms, quality of life and anxiety levels in response to the psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Additionally, in our previous paper about coping mechanisms and resilience in psychiatric trainees during the pandemic, we also found that good psychological mechanisms and adaptiveness decrease vulnerability to impairment [ 52 ]. Crișan et al, found similar results regarding the negative relation between dysfunctional coping and physical health among Romanian citizens during the current war in Ukraine [ 53 ]. From our knowledge, there is no research data regarding the correlation between coping strategies evaluated using COPE inventory and quality of life evaluated using WHOQOL-BREF among Romanian HCWs during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, in our previous paper about coping mechanisms and resilience in psychiatric trainees during the pandemic, we also found that good psychological mechanisms and adaptiveness decrease vulnerability to impairment [ 52 ]. Crișan et al, found similar results regarding the negative relation between dysfunctional coping and physical health among Romanian citizens during the current war in Ukraine [ 53 ]. From our knowledge, there is no research data regarding the correlation between coping strategies evaluated using COPE inventory and quality of life evaluated using WHOQOL-BREF among Romanian HCWs during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 70%
“…Both resources, both strategies and resilience, are effective in the face of the grief process at a general level (Rodríguez, 2018;Garfias-Royo et al, 2023;Mansoori et al, 2023), especially the type of grief exacerbated by violence, which is felt to be produced in the context of internal armed conflict (Acosta, 2018;Castillo & Palma, 2016;Crișan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%